A study on financial performance of Small and medium- sized enterprises in Vietnam - SANG, DANG VAN; HONG, NGUYEN THI THUY (The journal of contemporary issues in business and government, 2021)
Small and medium enterprises (SMEs) have shown the importance of the development strategy of the socialist-oriented market economy in Vietnam. The main objective of this study was to identify, evaluate, and to measure the attributes of financial performance of Small and Medium Enterprises (SMEs) in Vietnam. The study was based on a field survey using a semi-structured questionnaire on a sample of 150 accountants. But, only 120 filled questionnaires were satisfactory and therefore included in the analysis. By using seceral statistical analytical tools, i.e. descriptive statistics, Cronbach’s Alpha analysis, Independent T-test and ANOVA, the study has identified and measured four (4) attributes of financial performance of SMEs that have great effects on SMEs. There is, statistically, significant difference in the level of financial performance of SMEs in Vietnam from these different work experiences. There is not, statistically, significant difference in the level of financial performance of SMEs in Vietnam from these different business areas and between the mentioned three groups of job description. Based on the findings, some recommendations are given for SMEs to improve the financial performance.